The dynamics of caste relations in rural India - Ainapur, L. S. (Laxman Siddappa), 1933- (Jaipur : Rawat Publications, 1986)
Data based on villages from Dharwar District, Karnataka.
Includes bibliographical references and index.
Keywords: Caste -- India; Social classes -- India; India -- Rural conditions